Commuter Spouses : New Families in a Changing World - Lindemann, Danielle J. (Book collections on Project MUSE., 2019)
"Commuter spouses--married couples who live apart due to the demands of their dual professional careers--shed light on a series of broad shifts in the dynamics of marriage, family, gender roles, and professional careers in the United States"--